PLATFORM CONTROL SYSTEM AND COMMUNICATION SYSTEM FOR TRAIN SIMULATOR - PUTU ARIASTU KRISNADI RATA - NIM : 13214137 , NGAKAN
There is no Train Simulator in Indonesia which has motion simulation. There is one already, a train simulator with motion simulation in our world. Unfortunately, this simulator would not fit to be used in Indonesia. There are differences between Indonesia and this simulator modeled after in rail and locomotive type. Hence, it is preferred to build and develop a train simulator with motion simulation which will fit the rail and locomotive type used in Indonesia. The simulation platform is one of many integral parts of the train simulator which can be developed. There is many configurations to the Degree-of-Freedom of platform simulator. The opted movement is surge, roll, and pitch for this train platform. For the control of the platform, inverse kinematic would be required as to define the actuator movement which will move the platform. In addition to that, the communication system will also be developed to integrate all the subsystem in the train simulator. After implementation of the two system, Series of test and verification would be conducted towards the platform control system, inverse kinematic, and communication system. In the end, it would be shown that pitch movement would have 0.33 degree of maximum error, roll movement would have 1.01 degree of maximum error, and lastly, the surge movement would have no measurable error. Communication system would run with zero congestion and would be able to make the system run in real-time.